The Influence of Cyberspace, Computerization, and Technology on Information Systems - Syamsudin, Syamsudin; Ali, Hapzi (Siber International Journal of Education Technology (SIJET), 2024)
The Influence of Cyberspace, Computerization, and Technology on Information Systems is a scientific literature review article within the scope of ESBB. The aim of this article is to establish the influence between variables that will be used in subsequent research. The research objects are online libraries, Google Scholar, Mendeley, and other academic online media. The research method is library research sourced from e-books and open access e-journals, with qualitative descriptive analysis. The following are the findings of this analysis: 1) Cyberspace influences information systems; 2) Computerization influences information systems; and 3) Technology influences information systems.